Запозичена лексика сучасної української мови як інноваційна форма маркованої лексики - Жалко, Тетяна; Zhalko, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті з’ясовано особливості застосування стилістично маркованої лексики як основної складової частини авторського матеріалу. Наголошено, що саме унаслідок її використання текст набуває конкретного семантичного наповнення, а зміст матеріалу, незважаючи на тематику, завдяки вдалому використанню маркованих слів отримує неповторність та оригінальність. The article found particular application stylistically marked vocabulary as the main component of copyright material. It is emphasized that due to its use of text becomes specific semantic content, and its content, regardless of subject matter, thanks to the successful use of words gets marked individuality and originality. Practical application of marked words certainly enhances or degrades the effect of reading (above). Analysis of modern aspects of life convinces us that today's vocabulary deliberately formed and fixed tendency to enrich the language with new words and phrases. The main emphasis is on the fact that labeled vocabulary can express different stylistic value (emotional, evaluative, imaginative, intense and expressive) and is heterogeneous in terms of use. Therefore, the amount of vocabulary marked by several times the amount of general vocabulary.
Loanwords modern Ukrainian language as an innovative form marked vocabulary.
Keywords: запозичена лексика; маркована лексика; лексичний склад; інновації; неолексеми; loanwords vocabulary; marked vocabulary; lexical structure; innovation; neoleksemy